Analysis of lung and bronchus cancer incidence in the Republic of Belarus - Dubina, Maryna A.; Oceanov, Aleksey E.; Yaumenenka, Alesya A.; Mashevsky, Alexander A. (Journal of the Belarusian State University. Ecology, 2020)
The analysis of lung and bronchus cancer incidence in the Republic of Belarus for 1990−2018 is presented. The crude intensive and standardized (ASR World) incidence rates are calculated. The study revealed a pronounced decrease in standardized incidence rates among men living in cities, while among men living in rural areas the increased incidence rate over the study period was noted. Among the female population, a tendency towards an increase in the incidence rate was noted both in cities and in rural areas. A significant increase in the incidence rate of the rural population compared with the urban population was also noted, and these differences increase over time. A significant excess of the incidence rate of rural residents and its decrease among urban residents does not fit into the generally accepted idea of the prevailing effect of “urban” environmental factors on the increased risk of lung cancer. Thus, the presented estimate of the incidence rates of lung cancer is relevant and forms the basis for the subsequent study of the etiological causes of the development of the disease among various populations.